The value of financing through cross-border asset sales: Shareholder returns and liquidity - Borisova, Ginka; John, Kose; Salotti, Valentina (Journal of Corporate Finance, 2013)
We examine a sample of 1458 divestitures of domestic assets by U.S. firms to foreign and domestic buyers over the period 1998–2008. Cross-border asset sales yield higher abnormal returns to the seller than domestic sales. This incremental return is driven by liquidity-seeking sellers engaging in cross-border transactions. Larger seller returns in these international deals are associated with favorable economic conditions in foreign buyers' home markets relative to the U.S. We also find positive abnormal returns for buyers, albeit smaller than seller returns, but no significant difference between buyer returns in cross-border and domestic transactions.